The SEM (Structural Equation Modeling) analysis: project-based learning determinative factors in ethnoscience learning to developing 21st century competence - Jaja Jamaludin (Jurnal Scientia, 2024)
Education in the 21st century demands a transformation in learning approaches to produce graduates ready to face global challenges. One approach that is getting attention is Project Based Learning (PjBL) or project-based learning. In the context of science education, PjBL which is integrated with EtnoScience offers the potential to develop 21st-century competencies in students, such as critical thinking skills, collaboration, digital literacy, and entrepreneurship. This study aims to identify deter-minative factors of project-based learning with an EthnoScience approach in developing 21st-century competencies. The Structural Equation Modeling (SEM) analysis method is used to First, test the level of determination of Learning Objectives, Collaborative Work, Application of Skills and Knowledge, Initiative and Creativity, Development of Problem-Solving Skills, and Reflection and Self-Evaluation involved in this learning process. Second, to examine the influence of PjBL on 21st Century Competence.